A communities of practice approach to promoting regional circular economy innovation: evidence from East Wales. Issue 5 (4th May 2023) - Liu, Zheng; James, Steffan; Walpole, Gary; White, Gareth R. T.
ABSTRACT: With sustainability orientation and opportunities provided for economic growth, the circular economy is much promoted by the Welsh government in recent years. In this region, Communities of practice (CoP) are cultivated to link various industry sectors together, sharing knowledge and creating a practical solution to circular economy related challenges. While current literature provides the framework of a regional innovation ecosystem in the form of Triple Helix, the role of CoP is underexplored. The key research question of this paper is 'how can the CoP approach cultivate regional circular economy innovation?' Through an in-depth case study of the Communities of Circular Economy Innovation (CEIC) project in East Wales, the paper identifies the construct of CoP, its dynamic lifecycle, and the interaction between CoP and Triple Helix. Findings reveal that whilst universities and government play a leading role in innovation at early stages by deliberately establishing the CoP, the self-governance of CoP at later stages results in active influence on industry changes and policy designs. The paper contributes to the literature on micro-relations among regional innovation actors by highlighting the role of CoP in creating emerging new knowledge and tools. It also provides practical implications to industry and policy makers to promote a regional circular economy.